2014
DOI: 10.3109/03009742.2014.928946
|View full text |Cite
|
Sign up to set email alerts
|

Anti-high mobility group box 1 (anti-HMGB1) antibodies are not related to the occurrence of cutaneous lesions in systemic lupus erythematosus

Abstract: Based on the findings of the current study, it is unlikely that anti-HMGB1 antibodies play a role in the development of SLE cutaneous lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Previous studies have also demonstrated increased anti-HMGB1 levels in SLE patients [5,[9][10][11], and in a small study more specific antibodies directed to box A [10]. In this study it was shown that through epitope mapping multiple HMGB1 epitopes were recognized in SLE sera, with the major epitope mapping box A.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Previous studies have also demonstrated increased anti-HMGB1 levels in SLE patients [5,[9][10][11], and in a small study more specific antibodies directed to box A [10]. In this study it was shown that through epitope mapping multiple HMGB1 epitopes were recognized in SLE sera, with the major epitope mapping box A.…”
Section: Discussionsupporting
confidence: 54%
“…Autoantibodies against HMGB1 have been observed in patients with SLE [5,[9][10][11]. The clinical and/or pathological relevance of anti-HMGB1 antibodies is unclear, but their presence can interfere with the detection of HMGB1 in enzyme-linked immunosorbent assay (ELISA) systems [5,12].…”
Section: Introductionmentioning
confidence: 99%
“…Anti-HMGB1 antibodies have previously been reported in SLE patients [ 26 , 31 , 32 ] and there are also a few reports on elevated HMGB1 levels in SLE [ 24 26 , 40 ]. However, the clinical value and possible role of anti-HMGB1 antibodies in the pathogenesis of SLE remains elusive and further studies on this matter are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of HMGB1 are elevated in SLE patients and have been found to correlate positively with disease activity [ 24 27 ], and inversely with levels of complement proteins C3 and C4 [ 26 , 28 ]. HMGB1 may also serve as an autoantigen, leading to the production of anti-HMGB1 antibodies [ 26 , 29 32 ]. Anti-HMGB1/HMGB2 antibodies were first described as a type of “perinuclear” anti-neutrophil cytoplasm antibody (ANCA) in ulcerative colitis [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation